Features of the legal regulation of rent water bodies in the modern world - Костюченко, М. С. (Theory and practice of jurisprudence, 2016)
This article deals with current issues of lease water bodies in the present. We consider renting facilities, their legal status, usage, rental agents, especially their legal status and extent of possible behavior as participants lease.